Bioavailability, safety and tolerability of intravenous brivaracetam in healthy Japanese participants. (1st February 2022) - Yamamoto, Junichi; Ikeda, Kaori; Stockis, Armel
Abstract: We characterised the bioavailability, safety, and tolerability of brivaracetam 100 mg intravenous bolus and 15-min infusion versus oral reference tablet in 24 healthy Japanese participants. In this randomised, open-label, three-period crossover study, participants received three 100 mg single doses of brivaracetam, intravenous bolus, infusion, and oral tablets. Maximum plasma concentration (Cmax ), area under the plasma concentration-time curve from time zero to the time of last quantifiable concentration (AUCt ), and area under the plasma concentration-time curve extrapolated to infinity (AUCinf ), were compared using analysis of variance following logarithmic transformation. Bioavailability comparisons were based on the 90% confidence intervals (CIs) around the geometric least squares means ratios (intravenous:oral). Safety and tolerability were monitored throughout the study. The 90% CIs around AUCt and AUCinf ratios were entirely contained within the bioequivalence limits (0.80–1.25), but Cmax was outside the limits (90% CI: 1.77–2.08 and 1.44–1.70 for intravenous bolus and infusion, respectively). All participants completed the study. Brivaracetam was well tolerated. Because response to brivaracetam in epilepsy is related to exposure (AUC), no dose adjustment is warranted when switching from oral to intravenous dosing. However, investigations are needed to assess the safety and tolerability of intravenous administration in Japanese patients with epilepsy.